Charalampos Koutalakis, Cities and the Structural Funds. The Domestic Impact of EU Initiatives for Urban Development, Sak- koulas Publishers, Athens 2003, 304 σελ. - Σκιαδάς, Δημήτρης; Χρυσοχόου, Δημήτρης Ν. (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
[Δεν διατίθεται περίληψη / no abstract available]